RETRACTED: Skin dose estimation in adults undergoing diagnostic chest X-ray examinations at Al-Zahra Teaching Hospital in Wasit Governorate, Iraq - Jassim Ali Saeed; Hamza Zahraa Saad; Mraity Hussien Abid Ali Bakir; Abojassim Ali Abid; Mousa Rana Fadhil (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001